1994
DOI: 10.1002/mcs.1220060509
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical detection in open tubular column supercritical fluid chromatography using a platinum microelectrode and CO2/water as mobile phase

Abstract: Abstract.A miniaturized electrochemical detector for microcolumn separations has been developed. The detector was used in open tubular column supercritical fluid chromatography (SFC) with a mobile phase consisting of supercritical carbon dioxide with water below saturation. The detector is compatible with pressure programmed conditions, as is illustrated by the separation of ferrocene, acetylferrocene, and benzoylferrocene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…(142) and Dressman and Michael (143) described a heretofore uncommon detector for SFC, electrochemical detection. Almquist et al demonstrated that their miniaturized electrochemical detector was compatible with pressure-programmed elution (142). They used CO 2 containing water as mobile phase to separate and detect ferrocene and ferrocene derivatives.…”
Section: Sfc Instrumentation Techniques and Performancementioning
confidence: 99%
“…(142) and Dressman and Michael (143) described a heretofore uncommon detector for SFC, electrochemical detection. Almquist et al demonstrated that their miniaturized electrochemical detector was compatible with pressure-programmed elution (142). They used CO 2 containing water as mobile phase to separate and detect ferrocene and ferrocene derivatives.…”
Section: Sfc Instrumentation Techniques and Performancementioning
confidence: 99%
“…This was highly desirable because comparison of individual reports from the literature is difficult as the detection characteristics are determined by many aspects associated with detector design, parameter settings and separation conditions. In the context of small sample analysis it was interesting to explore whether the absolute LODs can be enhanced with the straightforward end-column microdisk detection approach [12,13] if the capillary id is reduced down to 2 mm. ACN-based NACE was applied to exploit the very reliable ED response in this medium [14] and to take advantage of the low viscosity of ACN, which facilitates filling and pressure injection in case of very small id capillaries.…”
Section: Introductionmentioning
confidence: 99%
“…They are widely used in electrochemical detectors employing a variety of different flow techniques, such as flow injection analysis [18,19], supercritical fluid chromatography [20,21] or capillary electrophoresis [22,23]. Significant elimination of the ohmic drop is one of the main advantage of microelectrodes over conventional-size electrodes.…”
Section: Introductionmentioning
confidence: 99%